Steroid-resistant intestinal aGVHD and refractory CMV and EBV infections complicated by haplo-HSCT were successfully rescued by FMT and CTL infusion. Issue 12 (December 2021) - Qi, Ling; Huang, Xianbao; He, Cong; Ji, Dexiang; Li, Fei
Haploidentical hematopoietic stem cell transplantation (haplo-HSCT) produces similar survival outcomes as HLA-matched sibling donor allogeneic HCST in younger patients with acquired severe aplastic anemia (SAA). This study reported a 29-years-old man with SAA and intracranial hemorrhage who underwent haplo-HSCT with a modified BU/CY + ATG conditioning regimen. Neutrophil and platelet engraftment were both achieved on day 14 after HSCT. The patient developed grade IV acute graft-versus-host disease (aGVHD) on day 20 and acquired cytomegalovirus (CMV) and Epstein–Barr virus (EBV) infections on day 47. After the failure of methylprednisolone, basiliximab, ruxolitinib, and antiviral treatment, the patient was diagnosed with steroid-resistant grade IV aGVHD and refractory CMV and EBV infections. We performed fecal microbiota transplantation and infused CMV- and EBV-specific cytotoxic T lymphocytes. After that the stool volume and frequency gradually decreased, and viral DNA was undetectable on day 80. This report provides helpful clinical experience for treating steroid-resistant aGVHD and refractory viral infections.